POSTOPERATIVE PAIN MANAGEMENT AFTER HYPOSPADIAS SURGERY IN CHILDREN - Koçinaj, Dëfrim; Todorovic, Lazar; Memeti, Shaban; Hasani, Antigona; Salihu, Era (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction: Postoperative pain after hypospadias surgery in children causes discomfort and may delay recovery. Effective pain management shortens hospital stays and improves satisfaction. Guidelines recommend a multimodal approach combining pharmacologic therapy, local or regional anesthesia, and nonpharmacologic strategies. Objective: To evaluate postoperative pain management in children undergoing hypospadias repair at the Department of Pediatric Surgery, University Clinical Center of Kosovo, and assess the effectiveness of different analgesic strategies. Materials and Methods: A prospective study included 60 children over 1 year old undergoing hypospadias repair between February and October 2023. Children with prior penile surgery were excluded. Pain was measured using the Faces Pain Scale. Analgesia included opioids, nonsteroidal anti-inflammatory drugs, caudal or penile blocks, or combinations, with supplemental acetaminophen or diclofenac for pain above mild. Results: Postoperative pain was reported in 42 children (70%), with some reporting multiple episodes. Nonsteroidal anti-inflammatory drugs alone were mostly associated with mild pain (15 reports) peaking at 2-6 hours. Caudal and penile blocks (n=10 each) produced mild to moderate pain within 2-6 hours. Penile block combined with nonsteroidal anti-inflammatory drugs (n=11) caused mainly mild pain. Caudal plus nonsteroidal anti-inflammatory drugs (n=2) and opioids plus nonsteroidal anti-inflammatory drugs (n=2) produced few scattered reports between 2-12 hours. Conclusions: All analgesic methods relieved pain, with modest benefit for caudal block. Multimodal strategies, though limited, provided high-quality analgesia. Broader use may reduce opioid reliance, improve comfort, and enhance recovery and satisfaction in pediatric patients. Key words: Analgesia, caudal block, NSAIDs, opioids, penile block, postoperative pain.